Adiponectin, IL-10 and metabolic syndrome in obese children andadolescents - Calcaterra, V.; De Amici, M.; Klersy, C.; Torre, et al., C. (Acta Biomedica Atenei Parmensis, 2009)
The metabolic syndrome (MetS) is a common basis for the development of atherogenic cardiovascular disease. Adiponectin has been demonstrated to be insulin-sensitizing and an anti-atherogenic factor and is considered a key of MetS. It was suggested that IL-10 may be involved in the inflammatory network of MetS in relation to adiponectin. We examined the relationship between adiponectin, IL-10 and MetS in pediatric obese patients. MetS components were assessed in 70 severely obese and 30 non-obese children and adolescents. Serum levels of adiponectin and IL-10 were measured in these subjects. Serum adiponectin levels were significantly lower (p<0.001) and levels of IL-10 were significantly higher (p=0.012) in obese subjects. MetS was present in 35.71% of obese patients. Patients with MetS showed a borderline significant decrease in serum adiponectin levels and significantly increased IL-10 levels when compared to those without MetS (p=0.051 and p=0.031, respectively); the differences in adiponectin and IL-10 values were controlled to the effect of BMI. No correlation between adiponectin and IL-10 levels was found. Our obese children showed hypoadiponectin and hyper-IL10 values. MetS was not associated with low IL-10. We probably observe a first phase of the complex mechanism implicated in the development of the MetS in children.